Aloe in Angola (Asphodelaceae: Alooideae) - R. R. Klopper; S. Matos; E. Figueiredo; G. F. Smith (Bothalia: African Biodiversity & Conservation, 2009)
Botanical exploration of Angola was virtually impossible during the almost three-decade-long civil war. With more areas becoming accessible, there is, however, a revived interest in the flora of this country. A total of 27 members of the genus Aloe L. have been recorded for Angola. It is not unlikely that new taxa will be discovered, and that the distribution ranges of others will be expanded now that botanical exploration in Angola has resumed. This manuscript provides a complete taxonomic treatment of the known Aloe taxa in Angola. It includes, amongst other information, identification keys, descriptions and distribution maps.